The perceived importance of cultural priority for global business operations: a study of Malaysian managers - Liu, Yi (Singapore Human Resources Institute, 2012)
The importance of understanding culture is vital for establishing effective business practices in the global arena. This study explored the perceived importance of cultural priority for global business operations among 132 Malaysian managers, who were attending the executive managerial development programme at Murdoch University, Perth, Western Australia. The empirical evidence shows that managerial perceptions and behaviours are affected by the cultural priority, but there is a transition towards a crossvergence management practice. These results are discussed in terms of the convergence – divergence – crossvergence debate against a backdrop of substantial transformation of the external environment of globalisation and advanced information technologies that are fast changing the traditional and contemporary business practices.